NUTRITIONAL STATUS OF PATIENTS WITH INFLAMMATORY BOWEL DISEASE AT HANOI MEDICAL UNIVERSITY HOSPITAL IN 2024-2025 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
The incidence of Inflammatory Bowel Disease (IBD) is rapidly increasing in developing countries in general and in Vietnam in particular. IBD patients, especially those with Crohn’s disease, mostly suffered from malnutrition when were diagnosed late, treated inappropriately, unresponsive or non-adherent to therapy.Study objective: To assess the nutritional status of patients with IBD at Hanoi Medical University Hospital during 2024–2025 and to describe some associated factors.Results: A cross-sectional descriptive study was conducted on 56 IBD patients at Hanoi Medical University Hospital from October 2024 to July 2025. The median age of the participants was 35.0 (27.0–47.75), ranging from 19 to 69 years, with the majority distributed in the 20–39 age group. The prevalence of malnutrition according to BMI, MUAC, and SGA/MNA in IBD patients was 33.9%, 32.1%, and 35.7%, respectively. Factors associated with malnutrition according to BMI included younger age and history of abdominal surgery. Factors associated with malnutrition according to SGA/MNA included history of abdominal surgery and active disease status.
Keywords: Inflammatory bowel disease (IBD), Crohn’s disease, Ulcerative colitis (UC), nutrition, protein-energy malnutrition, associated factors, Hanoi Medical University Hospital.